Agricultural economy of Bangladesh at the crossroads: achievements, challenges and potential for the future - Salim, Ruhul; Sabiha, N.; Rahman, S. (NOVA SCIENCE PUBLISH ERS, INC., 2018)
Bangladesh: Economic, Political and Social Issues has been organized around the economic, political and social opportunities and challenges of present Bangladesh. This book is the culmination of twelve chapters by twenty-four authors.